Alcohol‐mediated calcium signals dysregulate pro‐survival Snai2/PUMA/Bcl2 networks to promote p53‐mediated apoptosis in avian neural crest progenitors. Issue 12 (25th April 2019) - Flentke, George R.; Baulch, Joshua W.; Berres, Mark E.; Garic, Ana; Smith, Susan M.
Abstract: Background: Prenatal alcohol exposure causes distinctive craniofacial anomalies that arise, in part, from the apoptotic elimination of neural crest (NC) progenitors that form the face. This vulnerability of NC to alcohol is puzzling as they normally express the transcriptional repressor Snail1/2 (in chick Snai2), which suppresses apoptosis and promotes their migration. Here, we investigate alcohol's impact upon Snai2 function. Methods: Chick cranial NC cells were treated with acute alcohol (52 mM, 2 hr). We evaluated NC migration, gene expression, proliferation, and apoptosis thereafter. Results: Transient alcohol exposure induced Snai2 (191% ± 23%; p  = .003) and stimulated NC migration ( p  = .0092). An alcohol‐induced calcium transient mediated this Snai2 induction, and BAPTA‐AM blocked whereas ionomycin mimicked these pro‐migratory effects. Alcohol suppressed CyclinD1 protein content (59.1 ± 12%, p  = .007) and NC proliferation (19.7 ± 5.8%, p  < .001), but these Snai2‐enriched cells still apoptosed in response to alcohol. This was explained because alcohol induced p53 (198 ± 29%, p  = .023), and the p53 antagonist pifithrin‐α prevented their apoptosis. Moreover, alcohol counteracted Snai2's pro‐survival signals, and Bcl2 was repressed (68.5 ± 6.0% of controls, p  = .016) and PUMA was not induced, while ATM (1.32‐fold, p  = .01) and PTEN (1.30‐fold, p  = .028) were elevated. Conclusions: Alcohol's calcium transient uncouples the Snai2/p53 regulatory loop that normally prevents apoptosis during EMT. This represents a novel pathway in alcohol's neurotoxicity, and complements demonstrations that alcohol suppresses PUMA in mouse NC. We propose that the NCs migratory behavior, and their requirement for Snai2/p53 co‐expression, makes them vulnerable to stressors that dysregulate Snai2/p53 interactions, such as alcohol.